Multiple primary cancers: a case report and literature review - kambouche, faouzia; Riadh Mohammed , Mokhtar (International Journal of Medicine, 2023)
The fortuitous discovery of synchronous double primary cancers of the lung and stomach is relatively rare, but the discovery of triple primary cancers in one patient remains exceptional.The discovery of triple primary cancers in a single patient remains exceptional. This coexistence corresponds to the syndrome of multiple primary malignancies or multiple primary cancers (MPC). We present a case of synchronous association of squamous cell carcinoma of the lung and gastric adenocarcinoma with a history of mature squamous cell carcinoma of the larynx.